2023
DOI: 10.1001/jamaophthalmol.2023.5287
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and Perceived Barriers to Care in Diabetic Retinopathy Screening

Rohith Ravindranath,
Isaac A. Bernstein,
Karen S. Fernandez
et al.

Abstract: ImportanceRegular screening for diabetic retinopathy often is crucial for the health of patients with diabetes. However, many factors may be barriers to regular screening and associated with disparities in screening rates.ObjectiveTo evaluate the associations between visiting an eye care practitioner for diabetic retinopathy screening and factors related to overall health and social determinants of health, including socioeconomic status and health care access and utilization.Design, Setting, and ParticipantsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Furthermore, the study highlights a significant link between practitioner concordance and delayed eye care, influenced by factors including race, ethnicity, religion, and language. Further analysis will identify the key factors on concordance to overcome the overall health care barriers.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Furthermore, the study highlights a significant link between practitioner concordance and delayed eye care, influenced by factors including race, ethnicity, religion, and language. Further analysis will identify the key factors on concordance to overcome the overall health care barriers.…”
mentioning
confidence: 87%
“…To the Editor It was with great interest that we read the article by Ravindranath et al, which found that factors, such as food and housing insecurity, mental health, and practitioner concordance, hinder diabetic retinopathy screening. However, several limitations not necessarily completely addressed by the authors should be considered when interpreting the study’s conclusions.…”
mentioning
confidence: 99%
See 3 more Smart Citations